2015
DOI: 10.1016/j.apcatb.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of N2 and N2O peaks during and after the regeneration of lean NO trap

Abstract: a b s t r a c tThe dynamics and selectivity of N 2 and N 2 O formation during and after the regeneration of a commercial NO x storage catalyst containing Pt, Pd, Rh, Ba on Ce/Zr, Mg/Al and Al oxides was studied with high-speed FTIR and SpaciMS analyzers. The lean/rich cycling experiments (60 s/5 s and 60 s/3 s) were performed in the temperature range 200-400 • C, using H 2 , CO, and C 3 H 6 individually for the reduction of adsorbed NO x . Isotopically labeled 15 NO was employed in combination with Ar carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…We also proved experimentally that the secondary peaks originate from the reactions between residual stored NO x and adsorbed reduction intermediates remaining on the catalyst surface when switching back to lean phase, and their selectivity is insensitive to the presence of NO x in the gas phase [14]. Finally, we demonstrated that the secondary peaks diminish with a longer rich phase and more complete regeneration that leave less residual NO x and/or reduction intermediates on the catalyst surface [6,14].…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…We also proved experimentally that the secondary peaks originate from the reactions between residual stored NO x and adsorbed reduction intermediates remaining on the catalyst surface when switching back to lean phase, and their selectivity is insensitive to the presence of NO x in the gas phase [14]. Finally, we demonstrated that the secondary peaks diminish with a longer rich phase and more complete regeneration that leave less residual NO x and/or reduction intermediates on the catalyst surface [6,14].…”
Section: Introductionmentioning
confidence: 83%
“…Synthetic gases were used to perform a set of cycling experiments. A rapid switching 4-way valve was used to alternate between individual gas mixtures that were prepared independently in two lines [6,9,14]. The gas hourly space velocity (GHSV) was 30,000 h −1 and the experiments focused on the temperature range 200-250 • C where the contribution of secondary N 2 O and N 2 peaks is most significant.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations